INTEGRASI NILAI KEADILAN RESTORATIF DALAM PERSPEKTIF HUKUM ADAT BALI DAN KUHP NASIONAL - Nengah Nuarta; Dewa Putu Wahyu Jati Pradnyana (Fakultas Hukum Universitas Ngurah Rai, 2026)
The main problem in the integration of restorative justice values based on Balinese customary law into the national criminal law system lies in the absence of norms in the formulation of criminal law policies. Based on these problems, the following problems can be formulated: 1) How are the regulations and concepts of restorative justice in Balinese customary law and the National Criminal Code as part of Indonesian criminal law policy? 2) What is the model for integrating restorative justice values in Balinese customary law into the national criminal justice system to support the reform of Indonesian criminal law? This research is a normative legal research that focuses on the study of legal norms, related to the integration of restorative justice values based on local wisdom into the national criminal law system. The analysis of legal materials was carried out using the legal reasoning method. The regulation of restorative justice in the National Criminal Code has shown the direction of criminal law reform that recognizes the balance between the interests of perpetrators, victims, and the community and opens up space for recognition of living law. However, this recognition is still declarative and has not been followed by operational normative formulations regarding the position of customary law-based case resolution, especially Balinese customary law. The novelty of the proposed model lies in strengthening the position of customary settlements as the basis for terminating criminal justice processes and recognizing customary sanctions as a form of criminal punishment that restores social balance within the national penal system.